Solder alloys, solder balls and solder joints

By optimizing the alloy composition of Sn-Ag-Cu-Ni-P solder alloy, the conductivity and bonding strength of the brazed joint are improved, the problem of insufficient conductivity and bonding strength in the prior art is solved, and the problem of improved Finished rate.

CN115335186BActive Publication Date: 2024-12-31SENJU METAL IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180022148.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-19
Filing Date
2021-03-10
Publication Date
2024-12-31
Estimated Expiration
2041-03-10

AI Technical Summary

Technical Problem

The existing solder alloys have problems with insufficient conductivity and bonding strength in the brazed joints, resulting in low yield and easy to judge as poor conductivity.

Method used

By optimizing the alloy composition of Sn-Ag-Cu-Ni-P solder alloy, increasing the grain diameter and solidification starting temperature of Sn, suppressing supercooling, and selecting appropriate amounts of Ag, Cu, Ni and P elements to improve the pins The connectionability and bonding strength meet the specific element content range.

Benefits of technology

It realizes solder alloys with excellent pin connection and high bonding strength, which reduces errors in judgment of poor conduction and improves yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003850349910000131
    Figure BDA0003850349910000131
  • Figure BDA0003850349910000141
    Figure BDA0003850349910000141
  • Figure HDA0003850349920000011
    Figure HDA0003850349920000011
Patent Text Reader

Abstract

Provided are: a solder alloy, a solder ball and a solder joint that have excellent pin connectivity and high bonding strength. The solder alloy has the following alloy composition: in mass %, Ag: 0.8-1.5%, Cu: 0.1-1.0%, Ni: 0.01-0.10%, P: 0.006%-0.009%, and the balance is Sn. The preferred alloy composition satisfies equations (1) and (2). 2.0≤Ag×Cu×Ni / P≤25 (1), 0.500≤Sn×P≤0.778 (2). In the above equations (1) and (2), Ag, Cu, Ni, P and Sn are the contents (mass %) of the respective alloy compositions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to solder alloys, solder balls and solder joints. Background Art

[0002] In recent years, electronic devices are required to be highly integrated, thin and light. Along with this, electronic components mounted on electronic devices are also required to be miniaturized and thin. As a semiconductor package that meets these requirements, BGA (Ball Grid Array), a surface-mount package of a planar array type, is the mainstream. BGA has external electrode terminals on the mounting substrate of the package body, in which solder balls are arranged in a grid shape at equal intervals. After the solder balls are placed on the electrodes, they are heated and melted in a reflow oven together with the mounting substrate to form solder bumps.

[0003] In addition, in the existing BGA, Sn-Ag-Cu solder alloys represented by Sn-3.0Ag-0.5Cu are gradually used. However, compared with the Sn-Pb solder alloys used in the past, the solder alloys have poor wettability, so sometimes the interface between the electrode and the solder alloy is peeled off due to impact such as falling.

[0004] Therefore, Patent Document 1 discloses a solder alloy which improves drop impact resistance and suppresses discoloration by adding a predetermined amount of Ni and P to a Sn-Ag-Cu solder alloy. The following is described: If Ni is added to a Sn-Ag-Cu solder alloy, the Cu atomic sites of Cu6Sn5 formed at the interface are replaced with Ni, thereby relieving the stress of Cu6Sn5 and improving impact resistance.

[0005] Patent document 2 discloses a solder alloy that not only has impact resistance and yellowing suppression effects but also has high heat cycle resistance. The solder alloy contains any one or two or more of P, Ge, Al, and Si in a Sn-Ag-Cu solder alloy, and further contains Ni as one of the optional options.

[0006] Patent document 3 also discloses a solder alloy as a solder alloy that satisfies heat cycle resistance, impact resistance, and yellowing suppression, which contains Ag or Cu in a Sn-Sb-Ni solder alloy and contains a specified amount of at least one of P, Ge, Ga, and Co.

[0007] Patent Document 4 discloses a solder alloy containing at least one selected from Bi, In, Sb, P, and Ge in a Sn-Ag-Cu-Ni solder alloy in order to improve drop impact resistance and suppress non-fusion and discoloration. The document records that the drop impact resistance is improved by thinning the intermetallic compound layer of Cu6Sn5, and the non-fusion of the solder ball and the solder paste is suppressed by suppressing the precipitation of the intermetallic compound of Cu and Ni. In addition, it is also recorded that discoloration is suppressed by adding P, Ge, etc.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 5030442

[0011] Patent Document 2: Japanese Patent No. 4144415

[0012] Patent Document 3: Japanese Patent Application Publication No. 2004-141910

[0013] Patent Document 4: Japanese Patent No. 5633837 Summary of the invention

[0014] Problem that the invention aims to solve

[0015] As described above, the solder alloys disclosed in Patent Documents 1 to 4 show high impact resistance and discoloration resistance. In particular, the solder alloys disclosed in Patent Documents 2 and 3 also show excellent heat cycle resistance in addition to these, and the solder alloy disclosed in Patent Document 4 is an excellent invention that can also suppress non-fusion in addition to these.

[0016] Although it is believed that the solder alloys disclosed in Patent Documents 2 to 4 can form solder joints that are not easily broken, in order to confirm whether the solder joint is energized, it is necessary to directly insert the pin at the front end of the probe into the solder alloy constituting the solder joint to perform a continuity test. If the pin does not penetrate the solder alloy smoothly, even if the object to be inspected is conductive, it is judged as poor conductivity, which may cause problems such as unnecessary deterioration of the yield rate.

[0017] In addition, although the solder alloys described in Patent Documents 1 to 4 have been studied for impact resistance, discoloration resistance, and heat cycle resistance, one of the most important characteristics of solder joints is the bonding strength. When electronic components are mounted on a mounting substrate, both the mounting substrate and the electronic components are heated in a reflow furnace, but the linear expansion coefficients of the mounting substrate, the electronic components, and the solder alloy are different. Therefore, if the molten solder solidifies due to cooling, stress will be concentrated on the solder joint. If the bonding strength of the solder joint is weak, the solder joint will break.

[0018] As described above, the solder alloy used for forming the solder joint needs to satisfy the joint strength which is a mechanical property in addition to the pin contact property for confirming the electrical property of the solder joint.

[0019] It can be considered that the solder alloys described in Patent Documents 1 to 4 are optimized to achieve their respective purposes, but various properties need to be satisfied for solder joints, and therefore, the contents of the constituent elements constituting the solder alloys must be optimized according to the purpose. Therefore, in order to solve the above-mentioned problems, the alloy compositions of the solder alloys described in Patent Documents 1 to 4 must be re-examined in detail.

[0020] An object of the present invention is to provide a solder alloy, a solder ball, and a solder joint which are excellent in pin connection properties, have a high yield, and exhibit high bonding strength.

[0021] Solutions for solving problems

[0022] In the conduction test before productization, it is necessary to confirm the conduction of thousands to tens of thousands of joints on the printed circuit board. In the conduction test that has been performed so far, for example, a pin connection test is performed in which the pin at the front end of the probe is inserted into the solder alloy that constitutes the solder joint. In the case where the pin is not easy to penetrate the solder alloy, it is judged as poor conduction, and the inspection yield deteriorates. Therefore, it is necessary to prevent the solder joint that is originally conductive from being judged as not conductive. As mentioned above, the subject of the present invention is to provide: a solder alloy that is not easy to be judged as poor conduction and can obtain a joint with high bonding strength. As one of the means for solving the subject of the present invention, the inventors of the present invention focused on "the pin becomes easy to penetrate the solder alloy" and conducted research based on the metallurgical insights of the solder alloy.

[0023] Since the ease of insertion of the pin varies depending on the alloy composition of the solder alloy, even if the probe or the measuring device is improved, the ease of insertion of the pin cannot be improved. Therefore, in the current situation, it is necessary to improve the alloy composition of the solder alloy.

[0024] The inventors of the present invention first focused on the influence of the particle size of the crystalline phase constituting the solder alloy in order to improve the connectivity of the pins. If the grain diameter is large, each crystalline phase becomes prone to elastic deformation, and it is speculated that the pins will become easy to penetrate the solder alloy. Therefore, in order to increase the grain diameter of Sn in the Sn-Ag-Cu-Ni-P solder alloy, it is noted that the solidification start temperature of the solder alloy needs to be increased. In detail, it is noted that the higher the solidification start temperature, i.e., the liquidus temperature, of the solder alloy, the wider the temperature range until the solidification end temperature, i.e., the solidus temperature, is reached, and the more Sn as the initial phase will grow during solidification.

[0025] In addition, in order to increase the grain size, it is necessary to suppress overcooling during solidification. For this reason, it is considered that the alloy composition containing a specified amount of elements that act as solidification nuclei should be studied. However, if the liquidus temperature is too high, the solder alloy becomes difficult to melt at the normal reflow temperature. From these viewpoints, the inventors of the present invention have deliberately selected P, which was previously contained as a discoloration suppression element on the surface of the solder alloy, as an element that acts as a solidification nucleus. On this basis, the relationship with the content of each constituent element was investigated in detail in a manner that the liquidus temperature does not become too high. At this time, in order to improve the bonding strength, the need to make the intermetallic compounds formed at the bonding interface fine was also studied. In this study, in order to improve the pin connectivity and bonding strength of the Sn-Ag-Cu-Ni-P solder alloy disclosed in Patent Documents 1 to 4, the content of each constituent element was studied in detail.

[0026] The following insights were obtained: the content of P in the solder alloy disclosed in Patent Document 1 is not suitable, so the pin connectivity or bonding strength is poor. The following insights were obtained: the content of Ag or P in the solder alloy disclosed in Patent Document 2 is not suitable, so there is room for improvement in pin connectivity or bonding strength. The following insights were obtained: Sb is an essential element in the solder alloy disclosed in Patent Document 3, so there is room for improvement in pin connectivity. The following insights were obtained: the content of Ag and P in the solder alloy disclosed in Patent Document 4 is not suitable, so there is room for improvement in pin connectivity and bonding strength.

[0027] In addition, it is found that Ge, Al, Si, and Sb, which are considered as elements equivalent to P in these documents, do not function as solidification nuclei like P, and the wettability is deteriorated.

[0028] Therefore, the inventors selected only Ag, Cu, Ni and P as additive elements, and investigated the ranges of the optimal contents of Cu and Ni while optimizing the contents of Ag and P. As a result, they found that both the pin connection property and the bonding strength were excellent when the constituent elements were within the prescribed range, and thus completed the present invention.

[0029] The present invention obtained based on the above findings is as follows.

[0030] (1) A solder alloy characterized by having an alloy composition of, in mass %, 0.8 to 1.5% Ag, 0.1 to 1.0% Cu, 0.01 to 0.10% Ni, 0.006 to 0.009% P, and the balance Sn.

[0031] (2) The solder alloy according to (1) above, wherein the alloy composition satisfies the following formulas (1) and (2).

[0032] 2.0≤Ag×Cu×Ni / P≤25 (1)

[0033] 0.500≤Sn×P≤0.778 (2)

[0034] In the above formulas (1) and (2), Ag, Cu, Ni, P and Sn are the contents (mass %) of the respective alloy compositions.

[0035] (3) The solder alloy according to (1) or (2) above, wherein the alloy composition satisfies the following formula (3).

[0036] 221≤(Ag+Cu+Ni) / P≤309 (3) Formula

[0037] In the above formula (3), Ag, Cu, Ni and P are the contents (mass %) of the above alloy compositions.

[0038] (4) A solder alloy characterized in that it has the following alloy composition: in mass %, Ag: 0.8-1.5%, Cu: 0.1-1.0%, Ni: 0.01-0.10%, P: 0.005%-0.009%, and the balance is Sn, and the above alloy composition satisfies the following formulas (1) and (2).

[0039] 2.0≤Ag×Cu×Ni / P≤25 (1)

[0040] 0.500≤Sn×P≤0.778 (2)

[0041] In the above formulas (1) and (2), Ag, Cu, Ni, P and Sn are the contents (mass %) of the above alloy compositions.

[0042] (5) The solder alloy according to (4) above, wherein the alloy composition satisfies the following formula (3).

[0043] 221≤(Ag+Cu+Ni) / P≤309 (3) Formula

[0044] In the above formula (3), Ag, Cu, Ni and P are the contents (mass %) of the above alloy compositions.

[0045] (6) A solder ball formed of the solder alloy according to any one of (1) to (5) above.

[0046] (7) A solder joint comprising the solder alloy according to any one of (1) to (5) above. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1This is a diagram showing a DSC pattern curve for explaining the solidification temperature in the present invention. DETAILED DESCRIPTION

[0048] The present invention will be described in more detail below. In the present specification, "%" referring to the composition of the solder alloy means "mass %" unless otherwise specified.

[0049] 1. Alloy composition

[0050] (1) Ag: 0.8-1.5%

[0051] Ag is an element that lowers the melting point of the solder alloy and improves wettability. If the Ag content is less than 0.8%, the compound with Sn will not be fully generated, and a large amount of Sn and Cu compounds will be formed at the joint interface, which will deteriorate the joint strength. In addition, the melting point rises too much, and the solder alloy becomes difficult to melt. Furthermore, the wettability decreases and the joint strength decreases. The lower limit of the Ag content is 0.8% or more, preferably 1.0% or more, more preferably 1.1% or more, and particularly preferably 1.2% or more. On the other hand, if the Ag content is too much, the strength of the solder alloy is too high, the pin becomes difficult to penetrate, and the pin connectivity deteriorates. The upper limit of the Ag content is 1.5% or less, preferably 1.4% or less, and more preferably 1.3% or less.

[0052] (2) Cu: 0.1-1.0%

[0053] Cu is an element that improves the bonding strength by forming an appropriate amount of CuSn compound at the bonding interface. In addition, if the Cu content is within the above range, the solder alloy will deform appropriately, and therefore, high pin connectivity can be maintained. If the Cu content is less than 0.1%, the amount of CuSn compound precipitated is small, and the bonding strength will not be improved. The lower limit of the Cu content is 0.1% or more, preferably 0.3% or more, more preferably 0.4% or more, and particularly preferably 0.5% or more. On the other hand, if the Cu content exceeds 1.0%, the amount of CuSn compound precipitated becomes too much, and the bonding strength and pin connectivity are reduced. In addition, the melting point rises, and the liquidus temperature of the solder alloy is high and not easy to melt. The upper limit of the Cu content is 1.0% or less, preferably 0.8% or less, more preferably 0.7% or less, and particularly preferably 0.6% or less.

[0054] (3) Ni: 0.01-0.10%

[0055] Ni is an element that refines the CuSn compound formed at the bonding interface and improves bonding reliability. Furthermore, if the Ni content is within the above range, the solder alloy deforms appropriately, so that high pin connectivity can be maintained. If the Ni content is less than 0.01%, the miniaturization of the CuSn compound becomes insufficient and the bonding strength deteriorates. The lower limit of the Ni content is 0.01% or more, preferably 0.02% or more, more preferably 0.03% or more, further preferably 0.04% or more, and particularly preferably 0.05% or more. On the other hand, if the Ni content exceeds 0.10%, the NiSn compound precipitates, and the bonding strength and pin connectivity are reduced. In addition, the melting point rises and the wettability decreases, thereby reducing the bonding strength. In addition, the liquidus temperature of the solder alloy is high and it is not easy to melt. The upper limit of the Ni content is 0.10% or less, preferably 0.07% or less, and more preferably 0.06% or less.

[0056] (4) P: 0.006% to 0.009%

[0057] P is an element that acts as a solidification nucleus of the primary phase Sn when the molten solder is cooled, and contributes to the coarsening of the Sn crystal phase by promoting the high solidification point. Supercooling refers to a state of not solidifying at a temperature that solidifies in an equilibrium state, and can become a state in which the Sn phase that originally began to precipitate as the primary phase does not precipitate. Therefore, the present invention focuses on the P that is used as an element that functions on the surface of the solder alloy in order to inhibit oxidation and discoloration of the solder alloy in the past as a solidification nucleus. As a result, it is inferred that P is dispersed in the molten solder and functions as a solidification nucleus, supercooling is suppressed, Sn as the primary phase precipitates during solidification, and the grain diameter of the Sn crystal phase becomes larger.

[0058] If the P content is less than 0.006%, there will be few solidification nuclei, and even if it is cooled to the temperature at which the original crystal phase begins to precipitate, the crystal phase will not precipitate, resulting in an overcooling phenomenon. Therefore, solidification will occur rapidly below a certain temperature, the initial phase of Sn cannot become larger, and the grain diameter of Sn becomes smaller. As a result, the pin connectivity is reduced. The lower limit of the P content is more than 0.006%. On the other hand, if the P content is too much, a large amount of P oxide will be formed on the surface of the solder alloy, thereby reducing the bonding strength. In addition, the melting point rises and the wettability decreases, thereby reducing the bonding strength. The upper limit of the P content is less than 0.009%, preferably less than 0.008%, and more preferably less than 0.007%.

[0059] (5) Residue: Sn

[0060] The solder alloy of the present invention has a balance of Sn. In addition to the aforementioned elements, it may contain inevitable impurities. Even if inevitable impurities are contained, the aforementioned effects are not affected. In addition, even if the present invention contains undesirable elements as inevitable impurities, the effects of the present invention will not be impaired. Sb, Ge, Al, and Si do not function as solidification nuclei like P in the present invention. In addition, they will lead to a decrease in wettability, hinder normal wetting, and reduce bonding strength. Therefore, it is best not to contain them.

[0061] (6) Formula (1), Formula (2)

[0062] The present invention preferably satisfies the following formula (1) and formula (2).

[0063] 2.0≤Ag×Cu×Ni / P≤25 (1)

[0064] 0.500≤Sn×P≤0.778 (2)

[0065] In the above formulas (1) and (2), Ag, Cu, Ni, P and Sn are the contents (mass %) of the respective alloy compositions.

[0066] The solder alloy of the present invention preferably satisfies the formula (1). By satisfying the formula (1), the balance of the contents of Ag, Cu, Ni and P is optimized, thereby further improving the pin connectivity and the bonding strength. In the formula (1), P functions as a solidification nucleus of the Sn crystal phase, and Ag, Cu and Ni are elements that form compounds with Sn. Therefore, if the content ratio of Ag, Cu and Ni to P is appropriate, the two effects of the present invention are further improved.

[0067] The lower limit of formula (1) is preferably 2.0 or more, more preferably 3.3 or more, further preferably 4.0 or more, and particularly preferably 5.0 or more. The upper limit of formula (1) is preferably 25 or less, more preferably 20 or less, further preferably 15 or less, particularly preferably 10 or less, and most preferably 6.25 or less.

[0068] In addition, in formula (2), P contributes to increasing the grain size of Sn, so if the balance between the Sn content and the P content is appropriate, the pin connection property in particular will be improved. In addition, if the P content is appropriate relative to the Sn content, the formation of hard SnP compounds on the surface of the solder alloy will be suppressed, thereby achieving high pin connection property.

[0069] The lower limit of formula (2) is preferably 0.500 or more, more preferably 0.520 or more, further preferably 0.530 or more, further more preferably 0.550 or more, particularly preferably 0.584 or more, and most preferably 0.589 or more. The upper limit of formula (1) is preferably 0.778 or less, more preferably 0.750 or less, further preferably 0.700 or less, particularly preferably 0.650 or less, and most preferably 0.592 or less.

[0070] As described above, when the content ratio of Ag, Cu, Ni and P is optimized by satisfying equations (1) and (2), the two effects of the present invention are further improved. In this case, the P content may be 0.005% to 0.009%.

[0071] (7)(3)

[0072] The present invention preferably satisfies the following formula (3).

[0073] 221≤(Ag+Cu+Ni) / P≤309 (3) Formula

[0074] In the above formula (3), Ag, Cu, Ni and P are the contents (mass %) of the above alloy compositions.

[0075] The solder alloy of the present invention preferably satisfies formula (3). Formula (3) represents the balance between the total content of Ag, Cu, and Ni and the content of P. In the solder alloy of the present invention, Ag, Cu, and Ni are elements that can form compounds with Sn, and P is an element that contributes to the precipitation of the Sn phase. If formula (3) is satisfied, the Sn compound and the Sn phase precipitate in a good balance, thereby further improving the pin connectivity and bonding strength.

[0076] The lower limit of formula (3) is preferably 221 or more, more preferably 225 or more, further preferably 258 or more, further more preferably 275 or more, particularly preferably 286 or more, most preferably 288 or more, and may be 290 or more. The upper limit of formula (1) is preferably 309 or less, more preferably 308 or less, further preferably 300 or less, further more preferably 293 or less, particularly preferably 292 or less, and most preferably 291 or less.

[0077] (8) Solidification temperature (liquidus temperature) of solder alloy

[0078] The solder alloy of the present invention preferably has a solidification temperature, i.e., a liquidus temperature, which indicates a solidification start temperature, of 200°C or higher. In the Sn-Ag-Cu-Ni-P solder alloy of the present invention, if the liquidus temperature is 200°C or higher, the Sn crystal phase grows sufficiently when the molten solder solidifies, thereby obtaining good pin connection. In the present invention, the liquidus temperature is preferably 205°C or higher, particularly preferably 210°C or higher.

[0079] 2. Solder balls

[0080] The solder alloy of the present invention can be used as a solder ball. The solder ball of the present invention is used for forming bumps on electrodes and substrates of semiconductor packages such as BGA (ball grid array). The diameter of the solder ball of the present invention is preferably in the range of 1 to 1000 μm. The solder ball can be manufactured by a general solder ball manufacturing method.

[0081] 3. Brazing joints

[0082] The solder joint of the present invention is used to connect an IC chip in a semiconductor package to its substrate (interposer), or to connect a semiconductor package to a printed circuit board. That is, the solder joint of the present invention is called the connecting portion of the electrode, and can be formed using general soldering conditions.

[0083] 4. Pin connection test

[0084] The pin connectivity in the present invention is evaluated by a pin connectivity test in which the pin is inserted into a solder joint. The purpose of the ICT (In-circuit Test) for electrical inspection of the substrate based on pin connectivity is to determine whether the product is a good product. Therefore, the pin connectivity test is not limited to BGA components and chip components, and it can be said to be a universal test that can be performed anywhere as long as the electrical connection can be confirmed. The ICT device is a general device in substrate installation, not limited to BGA, and is used to confirm the conductivity of various components on a printed circuit board.

[0085] In addition, even if the conductivity can be confirmed in advance with a tester, it is necessary to evaluate the pin continuity of the prepared sample. The pin continuity test is a test for confirming the conductivity of the solder joint. The ease of probe penetration affects the yield rate. Therefore, in order to evaluate the influence of the ease of probe penetration, it is necessary to confirm the conductivity in advance in addition to the pin continuity test.

[0086] If the pin continuity of a solder bump that has not been confirmed to be conductive is evaluated and poor conductivity occurs, it is impossible to know whether the cause of the poor conductivity is the poor conductivity in the pin continuity test. Therefore, if the absence of poor conductivity is not confirmed in advance using a tester, the reliability of the pin continuity test will be impaired. Therefore, in order to perform the pin continuity test, it is necessary to confirm the conductivity of all solder bumps using a tester that measures resistance.

[0087] Here, if the continuity can be confirmed by a tester, the evaluation of the pin continuity may not be necessary. However, for the continuity evaluation of the solder joint, the pin continuity test is currently the mainstream. Therefore, in the field of electronic components, a solder alloy with less poor conduction in the pin continuity test is required. In more detail, in the continuity test of electronic components, it is necessary to confirm the conduction of a very large number of solder joints, such as thousands to tens of thousands, and in the continuity confirmation based on the usual tester, only the surface of the solder joint is contacted, so the measurement yield is very low. In recent years, automatic inspections based on flying probe testers are usually performed, but pin continuity tests are used in these automatic inspections. Therefore, even in the case where the conductivity of the prepared sample can be confirmed in advance with a tester, the evaluation of the pin continuity is still required.

[0088] 5. Others

[0089] The joining method using the solder alloy of the present invention can be performed according to conventional methods using, for example, a reflow method. The heating temperature can be appropriately adjusted according to the heat resistance of the chip and the liquidus temperature of the solder alloy. From the viewpoint of suppressing the thermal damage of the chip at a lower level, the melting temperature of the solder alloy can be a temperature approximately 20°C higher than the liquidus temperature. In addition, when the solder alloy of the present invention is used for joining, the cooling rate during solidification can be considered to further refine the structure. For example, the solder joint can be cooled at a cooling rate of 2 to 3°C / second or more. Other joining conditions can be appropriately adjusted according to the alloy composition of the solder alloy.

[0090] The solder alloy of the present invention can be produced by using a low α radiation material as its raw material. Such a low α radiation alloy can suppress soft errors when used for forming solder bumps around a memory.

[0091] Example

[0092] The solidification temperature, pin connection property and joint strength were evaluated as shown below for the solder alloys having the alloy compositions shown in Table 1. In addition, the tensile strength was also evaluated.

[0093] (1) Solidification temperature

[0094] Each solder alloy in Table 1 was prepared and the solidification temperature (liquidus temperature) of the molten solder was measured. The measurement method is as follows: using a DSC (Q2000: TA Instruments) device, the temperature was raised to 300°C and then cooled to 100°C at a cooling rate of 24°C / min. Since solidification is accompanied by an exothermic reaction, the DSC curve will show Figure 1 The solidification temperature measured in this embodiment, that is, the solidification start temperature (liquidus temperature during solidification), is the exothermic start temperature. Figure 1Point A.

[0095] When the solidification temperature was 200°C or higher, it was recorded as "0", and when it was lower than 200°C, it was recorded as "×".

[0096] (2) Pin connectivity

[0097] Solder balls with a diameter of 0.6 mm were made from the solder alloy shown in Table 1. The solder balls were soldered to a substrate with a thickness of 1.2 mm and an electrode size of 0.5 mm in diameter (Cu-OSP). The number of soldering was set to 60. The soldering conditions were as follows: a flux (manufactured by Senju Metal Industry Co., Ltd.: WF-6400) was applied to the electrode, and a reflow profile with a peak temperature of 245°C and a cooling rate of 2°C / sec was set, and soldering was performed using a reflow device (manufactured by Senju Metal Industry Co., Ltd.: SNR-615).

[0098] After confirming that all the samples were conductive, the lead was pushed in by 2 mm using IN-CIRCUIT HITESTER (Model: 1220) manufactured by HIOKI Corporation, and the solder bump was brought into contact with the tip of the lead, and each bump was inspected for conductivity.

[0099] The case where the ratio of the solder bumps to which current is supplied is 95% or more is marked as “⊚”, the case where the ratio is 90% or more and less than 95% is marked as “◯”, and the case where the ratio is less than 90% is marked as “×”.

[0100] (3) Bonding strength

[0101] Solder balls with a diameter of 0.6 mm were made from the solder alloy shown in Table 1. The solder balls were soldered to a substrate with a thickness of 1.2 mm and an electrode size of 0.5 mm in diameter (Cu-OSP). The number of soldering was set to 5. The soldering conditions were as follows: a flux (manufactured by Senju Metal Industry Co., Ltd.: WF-6400) was applied to the electrode, and a reflow profile with a peak temperature of 245°C and a cooling rate of 2°C / sec was set, and soldering was performed using a reflow device (manufactured by Senju Metal Industry Co., Ltd.: SNR-615).

[0102] The prepared samples were subjected to a shear strength test using a shear strength measuring apparatus (SERIES 4000HS manufactured by Nordson Dage) at a shear speed of 1000 mm / s.

[0103] The case where the average bonding strength of 5 is 4.6N or more is recorded as "◎", the case where it is 3.2N or more and less than 4.6N is recorded as "○", and the case where it is less than 3.2N is recorded as "×". In this embodiment, "◎" and "○" are evaluated as bonding strengths with no practical problems.

[0104] Tables 1 and 2 show the results.

[0105] [Table 1]

[0106]

[0107] [Table 2]

[0108]

[0109] Underlined text indicates outside the scope of the present invention.

[0110] As shown in Table 1, in Examples 1 to 25, the contents of the constituent elements are adjusted in any alloy composition, so the solidification temperature is high, the pin connection is excellent, and the bonding strength is also excellent. In addition, it can be seen that Examples 1 to 5, 9, 10, and 15 to 22 satisfy equations (1) to (3), so both the pin connection and the bonding strength are extremely excellent.

[0111] On the other hand, Comparative Examples 1 and 9 have high Ag contents, and therefore poor pin connection. Comparative Example 2 has low Ag content, Comparative Example 3 has high Cu content, Comparative Example 4 has low Cu content, Comparative Example 5 has high Ni content, Comparative Example 6 has low Ni content, and Comparative Example 7 has high P content, and therefore poor bonding strength. Comparative Example 8 has low P content, and therefore poor pin connection.

[0112] Comparative Example 10 contained Sb, and therefore had poor pin continuity. Comparative Examples 11 to 13 did not contain P, and contained Ge, Al, and Si, respectively, and therefore had poor characteristics of both pin continuity and bonding strength.

Claims

1. A solder alloy, characterized in that: The alloy composition is as follows: Ag: 0.8-1.5%, Cu: 0.1-1.0%, Ni: 0.01-0.10%, P: 0.006%-0.009%, and the balance is Sn, The alloy composition satisfies the following formula (2): 0.500≤Sn×P≤0.778 (2) In the formula (2), P and Sn are the contents in mass % of the respective alloy compositions.

2. The solder alloy according to claim 1, wherein The alloy composition satisfies the following formula (1): 2.0≤Ag×Cu×Ni / P≤25 (1) In the formula (1), Ag, Cu, Ni, and P are the contents of the alloy composition in mass %.

3. The solder alloy according to claim 1 or 2, wherein: The alloy composition satisfies the following formula (3): 221≤(Ag+Cu+Ni) / P≤309 (3) Formula In the formula (3), Ag, Cu, Ni and P are the contents of the alloy composition in mass %. 4 . A solder ball formed of the solder alloy according to claim 1 . 5 . A solder joint comprising the solder alloy according to claim 1 .